Financial anatomy of E4 Helsinki-Lahti shadow toll PPP-project - Leviakangas, Pekka; Wigan, M.; Haapasalo, H. (Emerald Group Publishing, 2013)
Purpose: The purpose of this paper is to investigate the returns to the investors and the state in private finance of road infrastructure. It uses an empirical case of the E4 Helsinki-Lahti road, which was built in 1995-1999 in Finland as the first real PPP-project. Design/methodology/approach: The analysis adopts an approach based on cash flow modelling of the project and the analyses show how the cash flows are formed and divided between the various stakeholders. The pure cash flow based approach to compare the economics of PPP vs traditional procurement of road infrastructure projects produced results that pose challenges to the logic, and pros and cons of shadow toll PPPs. Findings: The analysis shows that potential win-win situations are hard to find in shadow toll arrangements. This is largely due to the different discount rates used by investors and state. It is argued that the state does not include all the true costs in its appraisal of projects. Private investors, in principle and as a rule, price all of the relevant risks and uncertainties of which they are cognisant. Originality/value: The paper presents an analytical cash flow model that can be applied a wider range of PPP projects than simply to shadow toll roads. The paper contributes to the discussion on the viability of PPPs in different contexts.